You must remember this eaudiobook A novel. - Rosenfield, Kat (HarperAudio, 2023)
A Knives Out-style whodunnit with a twist of Taylor Jenkins Reid, You Must Remember This is an immersive Gothic mystery, with a long-ago love affair, icy death, and a rich family gone bad, from Kat Rosenfield, the acclaimed author of No One Will Miss Her. On Christmas Eve, eighty-five-year-old Miriam Caravasios steps onto the ice that surrounds her seaside estate on Maine's Mount Desert Island. As a younger woman, she used to steal out on winter nights to meet her lover, walking across the frozen reach to their secret meeting place. She knows the way—but not the year. Miriam, her mind clouded by dementia, doesn't hear the snap of thin ice until it's too late. Was it an accident? Suicide? Or worse: did someone lure the old woman onto the frozen reach, to her death? There are plenty of suspects; Miriam's fractured and complicated family has gathered in their Bar Harbor mansion to celebrate what everyone believed would likely be the matriarch's last Christmas. The guests include Delphine, Miriam's granddaughter, a frightened and insecure young woman who adored her grandmother, and Miriam's live-in aide, Adam, whom Delphine has been secretly dating. There is Miriam's former housekeeper, Shelly Dyer, who left the family's employment years ago under mysterious circumstances. There are Miriam's children: Theodora, who gave up everything to assume the role of caretaker; Diana, who seems just a little too eager to inherit her share of the estate; and Richard, whose longtime grudge against his mother has curdled into gleeful contempt at her deterioration. But it's Delphine who comes in for the greatest scrutiny when they learn the shocking news that Miriam's will cut off her children, leaving her granddaughter almost everything. As tensions rise, Delphine is emboldened to start asking questions: not just about her grandmother's death, but about her life, and the love story that defined it as the rest of her memories faded. The trail will take her into the past, into dark places — and eventually, onto thin ice.